The Interaction of the Effect of Principal’s Leadership and Educational Financing on Junior High School Teachers’ Performance - Hanim, Zaenab; Anita, Anita; Gede Mulawarman, Widyatmike; Sudadi, Sudadi (Jurnal Basicedu, 2023)
Because the principal oversees services for teaching and education personnel, teaching programs, students, educational financing, facilities, and community connections, the principal's leadership has a significant impact on teacher performance. This study intends to ascertain how the leadership of the principal and educational funding affect junior high school teachers' performance in the Mahakam Ulu District. With a sample of 104 teachers and a population of 128, this study is quantitative in nature. The methods of observation, surveys, and documentation are used to collect data. SPSS Statistics was utilized for data analysis, including regression and descriptive analysis. According to the study's findings, principle leadership has a 38% impact on teacher performance, education financing has a 55% impact, and principal leadership and financing together have a 66% impact. This study has implications for school leadership that will help administrators deliver instruction that is less reliant on outside sources. As a result, the principal is crucial to raising the standard of the school. In order to develop great schools, school principals must be revitalized because they have a significant impact on raising teacher performance and competency.